Understanding Emerging Market Sovereign Bond Yield Spread: Role of Default and Non-Default Determinants - Pratiwi, Adelia Surya (The Indonesian Capital Market Review, 2015)
This paper is motivated by the fact that emerging market assets size has been expanding and trying to use sovereign debt market as part of capital market as main research focus. It is highlighting the distinction between default and non-default determinants and examining their significance in explaining emerging market sovereign bond yield spread. Using Cross-Sectional Fixed-Effect Panel Estimator, we found that both default (as proxied by Credit Rating and Outlook Index) and non-default (as proxied by 3-month Fed Funds Futures) determinants has significant explanatory power to sovereign bond yield spread. Extensively, we also found the significance to add volatility of 3-month Fed Funds Futures and Fed Target Rate basis and volatility of advanced stock markets as variables to stand for non-default determinants in the model. The significance of the latter model is strengthened by higher forecasting as well as indicates the significant role of US market to emerging market sovereign bond market.